1993
DOI: 10.1017/s0889189300004859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensity of agronomic practices on a soil ecosystem

Abstract: The combination of several measures (organic matter accumulated, soil porosity, field soil respiration, CO2 evolved during incubation, and mineral N released) shows clearly that soil biological activity was enhanced in the systems that minimized tillage. Surprisingly, the abundance of earthworms, which are considered very sensitive to damage by tillage, did not always follow the same pattern. We do not know the reason for the response of earthworms, but in part it may have been an artifact of the interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
4
4
0
1
Order By: Relevance
“…Disadvantages with crop systems that rely on tillage include increased erosion risk (Edwards et al, 1993; McGregor et al, 1999), loss of soil structure, decrease in soil organic C levels (Studdert and Echeverria, 2000), and increases in machinery and fuel costs (Lu et al, 1999). Weil et al (1993) found that mineralizable N decreased with increasing intensity of tillage in five Maryland cropping systems.…”
supporting
confidence: 90%
“…Disadvantages with crop systems that rely on tillage include increased erosion risk (Edwards et al, 1993; McGregor et al, 1999), loss of soil structure, decrease in soil organic C levels (Studdert and Echeverria, 2000), and increases in machinery and fuel costs (Lu et al, 1999). Weil et al (1993) found that mineralizable N decreased with increasing intensity of tillage in five Maryland cropping systems.…”
supporting
confidence: 90%
“…The index derived from contrasting long-term sod and no sod in rotation (SDI SOD ) had the strongest level of agreement with farmer SQ ratings of the three indices. This is not surprising as the positive impact of sod on SQ has been described by many authors [47][48][49] . The index based on farmer ratings (SDI FR ) was calculated as a linear function of two parameters, C NMW and C SIR , which were selected because they optimized discrimination between unpaired good and poor rated soils.…”
Section: Relationships Between Sq Ratings By Farmers and Indices And supporting
confidence: 53%
“…Grass growth has been shown to elevate the values of soil microbiological indices including respiration, decomposition, organic C and N mineralization relative to cultivated crops (Follet and Schimel 1989;Weil et al 1993). In this study, the grass treatment restored the levels of MBC in soil to near or above those found in uncontaminated soil.…”
Section: Discussionsupporting
confidence: 47%
“…Soil microbiology plays a vital role in nutrient cycling, organic matter decomposition and pollutant degradation (Weil et al 1993;Turco et al 1994) and contributes heavily to the resiliency of a disturbed soil system (Karlen et al 1992). In a disturbed soil, microorganisms regulate restoration processes which make it possible for floral and faunal life to recolonize the soil.…”
mentioning
confidence: 99%